2022
DOI: 10.1021/acs.chemmater.2c00291
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Reaction Pathways in FeS2: Reversibility and the Electrochemical Formation of Fe3S4

Abstract: The present study has used a variety of characterization techniques to determine the products and reaction pathways involved in the rechargeable Li−FeS 2 system. We revisit both the initial lithiation and subsequent cycling of FeS 2 employing an ionic liquid electrolyte to investigate the intermediate and final charge products formed under varying thermal conditions (room temperature to 100 °C). The detection of Li 2 S and hexagonal FeS as the intermediate phases in the initial lithiation and the electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…31b Previous works have proposed that the sulfur loss of FeS 2 cathode accounts for the capacity fade in conventional organic electrolyte system, which is caused by the shuttle effect of polysulfide. 11 Obviously, there is no shuttle effect in ASSLB. Hence, we proposed a new insight that the sulfur loss of FeS 2 cathode in ASSLB manifests as accumulation in the form of inactive Li 2 S.…”
Section: Capacity Fading Mechanism Of Fesmentioning
confidence: 99%
See 1 more Smart Citation
“…31b Previous works have proposed that the sulfur loss of FeS 2 cathode accounts for the capacity fade in conventional organic electrolyte system, which is caused by the shuttle effect of polysulfide. 11 Obviously, there is no shuttle effect in ASSLB. Hence, we proposed a new insight that the sulfur loss of FeS 2 cathode in ASSLB manifests as accumulation in the form of inactive Li 2 S.…”
Section: Capacity Fading Mechanism Of Fesmentioning
confidence: 99%
“…Therefore, the capacity fade mechanism of FeS 2 gains extensive attention over the past few years. By analyzing the dissolution of polysulfide in 1,3‐dioxolane, Whang et al 11 demonstrated that the sulfur loss caused by shuttle effect accounts for the rapid capacity fade of FeS 2 . Ashby et al 12 pointed out that volume expansion and causing degradation of the conductive matrix is another important factor for the capacity fade.…”
Section: Introductionmentioning
confidence: 99%
“…For controversy (ii), researchers have recognized that the FeS 2 structure is not recoverable at 20–100 °C. [ 26–28 ] Researchers were eager to achieve the reproduction of FeS 2 after cycling at a high temperature (>400 °C). [ 29 ] The researchers analyzed this was feasible from the results of calorimetric measurements of chemically delithiated Li 2 FeS 2 and speculated the following reaction: FeS (hexagonal) + S197C$\xrightarrow{{{{197}}^ \circ {\rm{C}}}}$FeS 2 (orthorhombic)>2650.33emC$\xrightarrow{{ > 265{\ }^ \circ {\rm{C}}}}$FeS 2 (cubic).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, iron disulfide (FeS 2 ) is another prominent conversion cathode material of interest for Li-primary and thermal batteries due to its high theoretical energy density, low cost, thermal stability, and earth abundance . Li-FeS 2 is a well-known commercial Li-primary system with expansive effort put forth in demonstrating efficient electrochemical reversibility, allowing for high energy density cycling in secondary batteries. , Though it suffers from polysulfide limitations similar to Li–S, the formation of polysulfides in Li-FeS 2 may be mitigated more easily because the sulfur/polysulfide reaction mechanism is only one part of the overall Li-FeS 2 battery reaction mechanism for storing charge. Mitigation of polysulfide formation in Li-FeS 2 batteries is an active area of research, but a common mitigation is to use a limited voltage cycling window .…”
Section: Introductionmentioning
confidence: 99%